Adenoid Cystic Carcinoma Developed from the Parotid Gland to the Ear Lobe of a Young Woman. Issue 2 (February 2021) - Nojiri, Gaku; Kamimori, Tomoki; Uchiyama, Mizuki; Tomyo, Rei; Suga, Yasushi; Takamori, Kenji; Higo, Ryuzaburo; Hayashi, Ayato
Abstract : Summary: Adenoid cystic carcinoma (ACC) is a relatively rare malignant tumor. It is more common in women than in men and typically develops in the lacrimal, salivary, and breast glands. ACC of the external auditory canal (EAC) is exceedingly rare, and its invasion into the ear lobe is even more unusual. In this report, we present a case of ACC that presented as a mass on the surface of the ear lobe in a 28-year-old woman and was initially diagnosed as infected atheroma. For wide resection of the tumor, half of the entire auricula was resected and superficial parotidectomy was performed. After confirming no tumor cells on the surface of the facial nerve, the defect was reconstructed by the combination of platysma muscle flap to prevent Frey syndrome and free forearm flap for the ear lobe form. There was no recurrence or metastasis of the tumor, and Frey syndrome did not occur at 2 years and 8 months after surgery. The patient was satisfied with the result, oncologically and cosmetically. Even in young patients, comprehensive treatments (including diagnosis, resection, and reconstruction) are important in painful ear lobe masses.